OPTIMALISASI TEKNOLOGI AI: PENGARUH CHATGPT TERHADAP MOTIVASI BELAJAR MAHASISWA DI INSTITUT WIDYA PRATAMA - Siswanto, Victorianus Aries; Pudji Wahjuningsih, Tri; Indrayati (LPPM Universitas Muhammadiyah Muara Bungo, 2025)
The rapid advancement of Artificial Intelligence (AI) technology has significantly impacted various sectors, including education. One of the AI innovations currently gaining widespread use in education is ChatGPT. The implementation of ChatGPT in the teaching and learning process offers several conveniences for students. However, it also raises the question: how does the use of ChatGPT influence students' learning motivation? This study aims to analyze the effect of using ChatGPT, a rapidly developing AI innovation in education, on students' learning motivation at Widya Pratama Institute of Pekalongan. Using a quantitative approach, data were collected via a questionnaire with 103 respondents. The research instruments were tested for validity, reliability, and normality before being analyzed using correlation and linear regression tests. The results show a strong positive correlation between the use of ChatGPT and students' learning motivation, with a correlation coefficient (R) of 0.702. Further linear regression analysis confirms that the use of ChatGPT significantly affects students' learning motivation (significance value = 0.000 < 0.05). These findings suggest that integrating ChatGPT into university courses has the potential to enhance students' learning motivation. Keywords: ChatGPT, Learning Motivation, Artificial Intelligence, Higher Education.